2008
DOI: 10.1017/s0952675708001383
|View full text |Cite
|
Sign up to set email alerts
|

The processing of German word stress: evidence for the prosodic hierarchy

Abstract: The present paper explores whether the metrical foot is necessary for the description of prosodic systems. To this end, we present empirical findings on the perception of German word stress using event-related brain potentials as the dependent measure. A manipulation of the main stress position within three-syllable words revealed differential brain responses, which (a) correlated with the reorganisation of syllables into feet in stress violations, and (b) differed in strength depending on syllable weight. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
124
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(150 citation statements)
references
References 40 publications
25
124
1
Order By: Relevance
“…Domahs et al (2008) found evidence that the hierarchical organization of syllables and feet plays a role in word stress processing in German. In contrast, no such evidence was found for Polish (Domahs et al 2012).…”
Section: Rhythm Typementioning
confidence: 97%
See 1 more Smart Citation
“…Domahs et al (2008) found evidence that the hierarchical organization of syllables and feet plays a role in word stress processing in German. In contrast, no such evidence was found for Polish (Domahs et al 2012).…”
Section: Rhythm Typementioning
confidence: 97%
“…Along these lines, stress rules and their sensitivity to morphological and prosodic structure are a matter of debate (cf., e.g., Wurzel 1980;Giegerich 1985;Eisenberg 1991;Vennemann 1991). One possible account of German stress is based on the assumption that the prosodic foot is a domain of stress assignment, whereby several additional rules should be postulated in order to include the variety of different stress patterns in German (Wiese 2000;Domahs et al 2008). On the other hand, according to Jessen (1999), German stress is not predictable and as such cannot predict word boundaries (cf.…”
Section: Stress and Prominence Patternsmentioning
confidence: 99%
“…However, ERP studies of the last few years showed that prosodic information influence auditory processing on a lexical as well as on a structural stage (e.g., Steinhauer et al, 1999;Friedrich, Kotz, Friederici, & Alter, 2004;Knaus et al, 2007;Domahs et al, 2008). Moreover, the importance of rhythm and metrics has been revealed by various studies (Magne et al, 2007;SchmidtKassow & Kotz, 2009a,b;Rothermich et al, 2010Rothermich et al, , 2012Marie, Magne, & Besson, 2011).…”
Section: Previous Erp Studies On Rhythmic Processingmentioning
confidence: 99%
“…Liberman & Prince, 1977;Selkirk, 1984;Hayes, 1984;CouperKuhlen, 1986). Besides, German -as well as English -holds a trochaic standard pattern, i.e., metrical feet in which a stressed syllable precedes an unstressed syllable (Jessen, 1999;Domahs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation